Monitoring peroxisome dynamics using enhanced green fluorescent protein labeling in Alternaria alternata - Lu, Ziqi; Guo, Jian; Li, Qiang; Han, Yatao; Zhang, Zhen; Hao, Zhongna; Wang, Yanli; Sun, Guochang; Wang, Jiaoyu; Li, Ling (Frontiers in Microbiology, 2022)
Brown leaf spot on tobacco is a serious fungal disease caused by Alternaria alternata. Peroxisomes are organelles playing an important role in the development and infection in plant pathogenic fungi. But until now, it has not been reported on the peroxisome dynamics during the spore germination of A. alternata. To evaluate the roles of peroxisome in development of the fungus, in the present work, the eGFP combined with PTS2 were integrated into A. alternata to label the organelles, and as well an eGFP cassette carrying a nuclear located signal (NLS) was performed parallelly. The transformants containing the fusions emitted fluorescence in punctate patterns, and the fluorescence of eGFP-PTS2 located exactly in the peroxisomes while those of eGFP-NLS located in nucleus. Typical AaGB transformants were selected to investigate the peroxisome dynamics. The results showed that during spore germination the number of peroxisomes in the spores decreased gradually, but increased in germ tubes. In addition, when the transformants were cultured on lipid media, the number of peroxisomes increased and were present in a striped-distribution pattern. These findings give some clues for our understanding of peroxisomal function in the development of A. alternata.